Assessment of national reimbursement anticancer medications availability in China: based on a medical institution perspective - Wenxin Meng; Shudi Yang; Zhangke Wang; Jinping Xie; Rong Jiang (BMC, 2024)
Abstract Background High clinical value national reimbursement anticancer medications (NRAMs) are pivotal treatments for patients with cancer. However, the availability of NRAMs in medical institutions is unknown. This study aimed to assess the availability of NRAMs in national and provincial medical institutions. Methods This cross-sectional study utilized national health insurance data to access the availability of NRAMs in national and provincial medical institutions. Further statistical analyses and visualizations were conducted in terms of medical institution level and daily cost. Using the Spearman's rank correlation test (α = 0.05), we calculated the correlation between the availability rates of NRAMs and their negotiation access time, daily cost, per capita disposable income, provincial gross product, and number of policy releases. Results Overall, 81 NRAMs, with an average availability rate of approximately 1.01% nationwide, were included. There were significant differences between provinces for each drug, and the availability of NRAMs gradually decreased in tertiary (13.41%), secondary (1.58%), and primary medical institutions (< 0.05%). Differences were also observed in the availability rate of NRAMs in various daily drug cost ranges. Among the factors examined, negotiation access time (r1 = 0.425), daily cost (r2 = − 0.326), per capita disposable income (r3 = 0.645), provincial gross product (r4 = 0.433), and number of policy releases (r5 = 0.461) were all correlated with the availability of NRAMs. Conclusions The low availability of NRAMs in national and provincial medical institutions indicates that their willingness to equip NRAMs needs to be improved. All factors examined in this study affected the availability of NRAMs. Our findings can guide policymakers in improving relevant policies.